High-conjugation-degree block polymer, anion exchange membrane and preparation and electrochemical application of high-conjugation-degree block polymer and anion exchange membrane
By using high-conjugated block polymers, adjusting their skeleton and side chain structures, the balance of mechanical properties and ion conductivity of existing ion exchange materials in high temperature and high humidity environments is solved, and efficient ion transport and Mechanical stability.
Patent Information
- Application Number
- CN202510081745.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2045-01-20
AI Technical Summary
Existing ion exchange materials are difficult to meet high ion conductivity and good mechanical properties at the same time, resulting in insufficient stability and durability in environments such as high temperature, high humidity and chemical corrosion.
Using a high-conjugated block polymer, which contains a planar conjugated structure of a highly conjugated π system, enhances the interaction between polymer backbone by adjusting the ion concentration on the side chain, thereby enhancing the ionic conductivity and mechanical strength. .
The high ionic conductivity and mechanical strength of the anion exchange membrane are achieved, and the stability and durability of the material in complex environments are improved. It is suitable for electrochemical applications such as fuel cells and supercapacitors.
Smart Images

Figure CN119490633A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, and in particular to a highly conjugated block polymer, an anion exchange membrane, and preparation and electrochemical application thereof. Background Art
[0002] Ion exchange materials are a class of functional materials that can achieve specific functions by exchanging ions. They are usually composed of a matrix with fixed charges (linked to a polymer structure through chemical bonds) and mobile counter ions. They are widely used in water treatment (such as deionization, softening and desalination), fuel cells (as proton exchange membranes or anion exchange membranes), sensors, and pharmaceutical separation. In practical applications, the ionic conductivity and mechanical properties of ion exchange materials are key indicators. High ionic conductivity ensures efficient ion conduction, while good mechanical properties ensure the stability and durability of the material in complex environments. For example, in fuel cells, proton exchange membranes or anion exchange membranes require high ionic conductivity to improve energy conversion efficiency, and must have excellent mechanical properties to withstand harsh working conditions such as high temperature, high humidity and chemical corrosion. This performance balance is particularly important in automotive fuel cells and portable power sources. In addition, ion exchange membranes in reverse osmosis membranes and electrodeionization (EDI) equipment require fast ion conduction to improve purification efficiency, and are required to have sufficient mechanical strength to withstand high pressure environments, especially in applications such as industrial wastewater treatment and desalination. Ion exchange materials in high-precision electrochemical sensors require high conductivity to ensure sensitive signal transmission, while the mechanical properties of the material determine its service life and stability, especially in medical diagnosis and environmental monitoring, which require long-term continuous operation.
[0003] However, current materials often find it difficult to meet both requirements at the same time: in order to improve ionic conductivity, it may be necessary to increase the number of ion exchange groups or improve their distribution, but this may lead to an increase in the water absorption rate of the material. After absorbing too much water, the material will present a gel state, thus affecting its mechanical stability. In addition, adding a crosslinker can increase the strength of the polymer chain, but it will also reduce the mobility and void volume of the chain, affecting the migration of ions. Most of the anion exchange materials reported so far tend to have an ionic conductivity of only about 50 mS / cm when the tensile strength is 60-80 Mpa; and if the ionic conductivity is increased to 100 mS / cm, the tensile strength will drop sharply to 20-40 Mpa. For example: Steven Holdcroft's experimental group at Simon Fraser University in Canada published a class of anion exchange materials based on polybenzimidazole, placing imidazole cations on the main chain of the polymer. Due to the large number of protective groups around the active ions, the alkali stability of the material is improved, and its tensile strength is about 70 Mpa. However, the Coulomb force between the ion pairs of the material is weakened, resulting in weak ion transmission and a conductivity of about 70 mS / cm. Professor Chulsung Bae of Rensselaer Polytechnic Institute disclosed the work of polyaryl polymer electrolytes, which separated the charge groups from the polymer backbone using carbon chains, and also formed nanoscale ion channels through block and main chain design. This design idea makes the material have better ion conductivity (80-90 mS / cm@60 ℃), but it sacrifices the mechanical strength of the membrane to a certain extent (30 Mpa tensile strength).
[0004] Therefore, achieving a balance between ionic conductivity and mechanical properties is an important challenge in the research of ion exchange materials. Summary of the invention
[0005] The first objective of the present invention is to provide a highly conjugated block polymer in view of the deficiencies in the prior art. The block polymer has a highly conjugated π system, which utilizes a larger planar conjugated structure to enhance the interaction between polymer skeletons, and then simultaneously improves the ionic conductivity and mechanical strength by adjusting the ion concentration on the side chain.
[0006] A highly conjugated block polymer comprises a structural unit represented by the following formula (I):
[0007]
[0008] (I)
[0009] wherein n, m are the number of repeating units; n is an integer from 1 to 2000; m is an integer from 1 to 2000;
[0010] Ar1 is selected from one of the following structural fragments:
[0011] , , or ;
[0012] Ar2 is selected from one of the following structural fragments:
[0013]
[0014] The values of x1 and x2 are 0-10;
[0015] LK1 and LK2 are linking groups, independently selected from or ;
[0016] is an ionic group, wherein the cationic group ( ) is selected from one of the following structural fragments:
[0017]
[0018] Anionic groups ( ) is selected from one of the following structural fragments:
[0019]
[0020] R1 is an ionic group or a nonionic group; when R1 is an ionic group, its definition is the same as When R1 is a nonionic group, it is selected from one of the following structural fragments:
[0021]
[0022] Preferably, Ar1 is selected from or .
[0023] Preferably, EWG is selected from one of the following structural fragments:
[0024]
[0025] Preferably, the highly conjugated block polymer is selected from one of the following structural formulas:
[0026]
[0027]
[0028]
[0029]
[0030]
[0031]
[0032] The second object of the present invention is to provide a method for preparing the above-mentioned highly conjugated block polymer, comprising the following steps (when LK1 and LK2 are both When, compound 1-17X):
[0033] (1) Ar1, EWG(CO)Rii, Ar2, and EWG(CO)R1 are mixed and dissolved in a solvent, and reacted under the action of a catalyst to generate a precursor;
[0034]
[0035] Rii ;
[0036] Preferably, the solvent is an organic solvent, more preferably one of dichloromethane, chloroform, tetrachloromethane or chlorobenzene.
[0037] Preferably, the catalyst is a strong acid, more preferably one or a mixture of concentrated sulfuric acid, concentrated nitric acid, trifluoroacetic acid, trifluoromethanesulfonic acid.
[0038] (2) dissolving the precursor in a solvent, adding a nucleophilic reagent to react, quenching and eluting, and then adding a salt solution to perform ion exchange to obtain the highly conjugated block polymer;
[0039]
[0040] Preferably, the solvent is an organic solvent, more preferably tetrahydrofuran, dichloromethane, chloroform, methyl pyrrolidone, ethylene carbonate, and the like.
[0041] Or comprising the following steps (when LK1 and LK2 are independently selected from or When, compound 18-23X):
[0042] (1) Ar1, EWG(CO)Rii, Ar2, and EWG(CO)R1 are mixed and dissolved in a solvent, and reacted under the action of a catalyst to generate a polymer precursor;
[0043]
[0044] Rii ;
[0045] Preferably, the solvent is an organic solvent, more preferably one of dichloromethane, chloroform, tetrachloromethane or chlorobenzene.
[0046] Preferably, the catalyst is a strong acid, more preferably one or a mixture of concentrated sulfuric acid, concentrated nitric acid, trifluoroacetic acid, trifluoromethanesulfonic acid.
[0047] (2) The precursor is dissolved in an organic solvent for functionalization to obtain an intermediate, which is then reacted with a linker. The mixture is mixed, a nucleophilic reagent is added for reaction, and a salt solution is added for ion exchange after quenching and elution to obtain the highly conjugated block polymer.
[0048]
[0049] Wherein Y6 and Y7 are independently selected from F, Cl, Br or .
[0050] The third object of the present invention is to provide an anion exchange membrane prepared from the above-mentioned highly conjugated block polymer. The preparation process is:
[0051] The highly conjugated block polymer is dissolved in an organic solvent to prepare a slurry, which is then coated on a substrate by a roll-to-roll process, screen printing or doctor blade casting. The organic solvent in the slurry is evaporated by drying to solidify the highly conjugated block polymer on the surface of the substrate to form a film, which is then peeled off to obtain the anion exchange membrane; wherein the organic solvent is one or a mixed solution of two or more of ethanol, methanol, isopropanol, trimethyl sulfoxide, methyl pyrrolidone and ethylene carbonate.
[0052] The fourth object of the present invention is to provide the use of the above anion exchange membrane in electrochemistry.
[0053] The applications include: preparation of fuel cells, preparation of supercapacitors, preparation of organic liquid flow batteries, electrolysis of water, electrolysis of CO2, electrolysis of CO, heavy metal separation equipment, CO2 purification equipment, electrically driven CO2 enrichment equipment, lithium salt recovery, and as metal-air battery separators.
[0054] Compared with the prior art, the present invention has the following beneficial effects:
[0055] 1. The present invention uses highly conjugated, planar skeleton groups to strengthen the pi-pi interaction on the polymer main chain in a non-polar phase to prepare a highly conjugated block polymer, and the anion exchange membrane prepared thereby has stronger mechanical strength;
[0056] 2. The present invention regulates the ratio of the backbone block (Ar1+Ar2) to the ionic groups on the side chain (1:1-10 molar equivalent), thereby improving the mechanical strength and the overall ionic conductivity of the material;
[0057] 3. The present invention introduces cyclic ionic functional groups, thereby improving the chemical stability of the material in the use environment.
[0058] In summary, the present invention can simultaneously improve the ionic conductivity and mechanical strength of the anion exchange membrane, so as to regulate the self-assembly mode within the material, so that the material forms a nanostructure to enhance ion transmission; by adjusting the size of the conjugated structure of the polymer backbone segment, the prepared material properties are regulated in water absorption, mechanical properties and ion transmission efficiency to increase the energy consumption and stability of the membrane material in application scenarios such as electrochemical devices and separation devices. The membrane material obtained by the present invention can be used in fuel cells, organic liquid flow batteries, electrolysis of water, electrolysis of CO2, electrolysis of CO, supercapacitors, lithium-ion battery diaphragms, lithium-ion battery electrolytes, metal-air battery diaphragms, heavy metal separation in water, CO2 purification, electrically driven CO2 enrichment, Li salt recovery and other application scenarios that require high-quality electrolytes, providing more efficient and stable material solutions for downstream electrochemical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 The gel chromatography data of intermediates 1a-5a.
[0060] Figure 2 This is the hydrogen nuclear magnetic spectrum of polymer 22X.
[0061] Figure 3 It is a comparison chart of material performance test data of preferred polymers 18X, 19X, and 21X.
[0062] Figure 4 A is the water electrolysis test process and test bench design, B is the test battery structure, and C is the actual test battery.
[0063] Figure 5 The voltage data of polymer 22OH after running for 1000 hours in the electrolytic water test environment. DETAILED DESCRIPTION
[0064] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0065] Embodiment 1-17:
[0066] As mentioned above, the first step of synthesis of the preferred structure 1X-17X is as follows:
[0067]
[0068] After the intermediate is prepared, the preferred synthesis of structure 1X-5X is as follows:
[0069]
[0070]
[0071] The synthesis method of intermediates 1a-5a is as follows:
[0072] 1,1'-binaphthyl (9.9 g, 39 mmol), 4-bromo-1,1,1-trifluoro-2-butanone (8.7 g, 40 mmol) were placed in a two-necked round-bottom flask, and dichloromethane (40 mL) was added; the mixture was dissolved by mechanical stirring at room temperature. The reaction system was cooled to 0 °C, and a trifluoromethanesulfonic acid / trifluoroacetic acid mixed solution (1:1, 20 g) was slowly added dropwise. After the addition was complete, the mixture was stirred at 0 °C for 10 min, and the reaction system was moved to a 30 °C water bath. After the system temperature reached 30 °C, the molecular weight growth was detected by gel chromatography every half an hour. When the average molecular weight reached 28 KDa, the reaction solution was poured into 800 mL of cold 1:1 methanol / water solution to precipitate a solid. The solid was collected and washed with deionized water. Drying and crushing gave a light green powder 1a (16.6 g) with a yield of 90%. 1 H NMR (500MHz CDCl3) δ8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2Hs), 3.4 (m, 2Hs), 2.3(m, 2Hs), 1.6 (m, 2Hs).
[0073] The synthesis method of 2a was similar to that of 1a, and the reaction was terminated at 140 KDa. The product was dried and crushed to obtain a light green powder 2a (17.8 g) with a yield of 97%. 1 H NMR (500 MHz CDCl3) δ8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2Hs), 3.4 (m, 2Hs), 2.3(m,2Hs), 1.6 (m, 2Hs).
[0074] The synthesis method of 3a was similar to that of 1a, and the reaction was terminated at 253 KDa. The product was dried and crushed to obtain a light green powder 1a (18.0 g) with a yield of 98%. 1 H NMR (500 MHz CDCl3) δ8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2Hs), 3.4 (m, 2Hs), 2.3(m, 2Hs), 1.7(m, 2Hs).
[0075] The synthesis method of 4a was similar to that of 1a, except that the amount of dichloromethane was increased to 80 mL and the reaction system was refluxed at 45 ° C. The molecular weight of 4a was 460 KDa when the reaction was terminated, and the product was light green fiber 1a (18.3 g) with a yield of 99%. 1 H NMR (500MHz CDCl3) δ8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2Hs), 3.4 (m, 2Hs), 2.3(m,2Hs), 1.7 (m, 2Hs).
[0076] The synthesis method of 5a was similar to that of 1a, except that the amount of dichloromethane was increased to 80 mL and the reaction system was refluxed at 45 °C. The molecular weight of 5a was 863 KDa, and the product was a tea green block (18.0 g) after drying, with a yield of 98%. 1 H NMR (500 MHz CDCl3) δ8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2Hs), 3.4 (m, 2Hs), 2.3(m,2Hs), 1.7 (m, 2Hs).
[0077] The preferred structural intermediate 1b and the preferred structural intermediate 1X are synthesized as follows:
[0078] Dissolve 1a (10 g, 21.2 mmol) in 200 mL of tetrahydrofuran in a three-necked round-bottom flask, add methylimidazole (1.73 g, 21.2 mmol), and protect the reaction system with nitrogen. Reflux the reaction system at 60 °C for 72 hours. When the reaction becomes turbid, add 100 mL of ethanol. Use TLC to detect and find that the methylimidazole is completely consumed. Pour the reaction system into 2 L of anhydrous ether to obtain a flocculent precipitate. After drying the precipitate, wash it with clean water three times, each time for 24 hours. Dry and grind to obtain 9.9 g of light yellow powder with a yield of 85.3%. 1 H NMR (500 MHz DMSO-d6) δ9.2 (m, 1), 8.0-8.1 (m, 2H), 7.6-8.0 (m, 10Hs), 7.2-7.3 (m, 2Hs), 4.2 (m, 3Hs), 2.4 (m, 2Hs), 1.8 (m, 2Hs). Dissolve 0.5 g of 1b in 18 mL of 1:1 tetrahydrofuran / methanol solution, filter (0.2 μm filter) and spread the solution on a flat PTFE plate (25 cm 2), heat the surface to 50 ℃. After the solvent is completely evaporated (about 24 hours), soak it in water to remove the membrane. Roll up the membrane material and put it into a 20cm high round container, add 100 mL of 1 M NaCl solution, and exchange it at room temperature for 72 hours on a shaker, replacing the NaCl solution every 24 hours. After the exchange is completed, wash it with deionized water until the ion conductivity of the washing liquid is less than 3μS / cm. 1 Cl membrane material is obtained, and 1 OH membrane is obtained using the same method using 1 M NaOH as the exchange liquid, and 1 KHCO3 membrane material (1X) is obtained using 1 MKHCO3 as the exchange liquid. Elemental analysis of the 1X membrane material shows that the Br content is less than 0.1wt%.
[0079] The preferred structural intermediate 2b and the preferred structural intermediate 2X were synthesized similarly to 1b and 1X. 2a (10 g, 21.2 mmol) and N-methyldicyclohexylamine (4.13 g, 21.2 mmol) were used as reaction reagents, propylene carbonate (PC) was used as reaction solvent, and the reaction temperature was 90 °C. The product 2b was a yellow-brown powder of 12.1 g, with a yield of 86%. 1 H NMR (500 MHz DMSO-d6) δ8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2Hs), 3.1 (m, 4Hs), 2.9 (m, 3Hs), 2.6 (m, 2Hs), 1.2-2.0 (m, 22Hs). The 2X membrane material was prepared in the same way as 1X, and the elemental analysis showed that the Br content was less than 0.1 wt%.
[0080] The preferred structural intermediate 3b and preferred structural intermediate 3X were synthesized in the same manner as 1b and 1X. The reaction reagents used were pyridine (1.67 g, 21.2 mmol) and 3a (10 g, 21.2 mmol). The product 3b was a dark brown powder of 11.0 g with a yield of 94.3%. 1 H NMR (500MHz DMSO-d6) δ9 (m, 2Hs), 8.5 (m, 2Hs), 8.1 (m, 2Hs), 7.9-8.0 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2Hs), 4.5 (m, 2Hs), 2.4 (m, 2Hs), 1.7 (m, 2Hs). The preparation method of 3X membrane material is similar to that of 1X, the solvent is cyclopentane, and the drying temperature is 90 °C. The exchange process is the same as that of 1X, and the elemental analysis shows that the Br content of 3X membrane is less than 0.1 wt%.
[0081] The preferred structural intermediates 4b and 4X were synthesized in the same manner as 1b and 1X. Intermediate 4a (10 g, 21.2 mmol) was dissolved in 400 mL tetrahydrofuran, and dodecyldimethyl tertiary amine (4.5 g, 21.2 mmol) was used as the reaction reagent. The product 4b was 12.8 g of light brown powder with a yield of 88.3%. 1 H NMR (500 MHz DMSO-d6) δ8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2Hs), 3.1 (m, 4Hs), 2.9 (m, 3Hs), 2.6 (m, 2Hs), 1.7 (m, 2Hs), 1.0-1.5 (m, 23.2Hs). The preparation method of 4X membrane material is similar to that of 1X, with propylene carbonate (PC) as solvent and drying temperature of 90 °C. The ion exchange method after demolding is the same as that of 1X, and the elemental analysis shows that the Br content in 4X membrane is less than 0.1 wt%.
[0082] The preferred structural intermediates 5b and 5X were synthesized similarly to 1b and 1X. Intermediate 5a (10 g, 21.2 mmol) was dissolved in 400 mL tetrahydrofuran, and N,N-dimethylhexylamine (2.7 g, 21 mmol) was used as the reaction reagent. The product 5b was 11.9 g of light yellow powder with a yield of 93.4%. 1 H NMR (500 MHz DMSO-d6) δ8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2Hs), 3.2 (m, 4Hs), 3.0 (m, 6Hs), 2.6 (m, 2Hs), 1.7 (m, 2Hs), 1.0-1.5 (m, 10.9Hs). The preparation method of 5X membrane material is the same as that of 1X membrane material. The Br content of the product 5X membrane is less than 0.1 wt% in elemental analysis.
[0083] The preferred synthesis method of structure 6X-8X is as follows:
[0084]
[0085] Polymerization reaction gave 6a-8a:
[0086] 1,1'-binaphthyl (9.9 g, 39 mmol), 5-bromo-1,1,1-trifluoro-2-hexanone (4.7 g, 20 mmol), trifluoroacetone (2.2 g, 20 mmol) were placed in a two-necked round-bottom flask, and dichloromethane (40 mL) was added; the mixture was dissolved by mechanical stirring at room temperature. The reaction system was cooled to 0 °C, and a trifluoromethanesulfonic acid / trifluoroacetic acid mixed solution (1:1, 20 g) was slowly added dropwise. After the addition was complete, the mixture was stirred at 0 °C for 10 min, and the reaction system was moved to a 30 °C water bath. After the system temperature reached 30 °C, the molecular weight growth was detected by gel chromatography every half an hour. When the average molecular weight reached 215 KDa, the reaction solution was poured into 800 mL of cold 1:1 methanol / water solution to precipitate a solid. The solid was collected and washed with deionized water. The product was dried and crushed to obtain a matcha-colored powder 7a (15.8 g) with a yield of 95%. 1 H NMR (500 MHz CDCl3) δ8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2Hs), 3.4 (m, 1Hs), 2.3-2.4 (m, 2.5Hs), 1.2-1.4 (m, 2Hs). NMR and molecular weight calculation gave n:m=251:251.
[0087] The same method as 7a was used to synthesize 6a. The reactant ratio was adjusted to 1,1'-binaphthyl (9.9 g, 39 mmol), 6-bromo-1,1,1-trifluoro-2-hexanone (8.4 g, 36 mmol), and trifluoroacetone (0.4 g, 4 mmol). The product was a light green tea powder (18.1 g) with a yield of 98% and a molecular weight of 230 KDa. 1 H NMR (500 MHz CDCl3) δ8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2Hs), 3.4 (m, 1.8Hs), 2.3-2.4(m, 2.1Hs),1.2-1.4 (m, 3.7Hs). NMR, molecular weight calculation gave n:m=436:48.
[0088] 8a was synthesized using the same method as 7a, with the reactant ratio adjusted to 1,1'-binaphthyl (9.9 g, 39 mmol), 6-bromo-1,1,1-trifluoro-2-hexanone (0.9 g, 4 mmol), and trifluoroacetone (4.04 g, 36 mmol). The product was a matcha-colored powder (14.1 g) with a yield of 96% and a molecular weight of 213 KDa. 1H NMR (500 MHz CDCl3) δ8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2Hs), 3.4 (m, 0.2Hs), 2.3-2.4(m,2.9Hs), 1.2-1.4(m, 0.4Hs). NMR, molecular weight calculation gave n:m=56:507.
[0089] The preferred structural intermediate 6b and the preferred structural intermediate 6X were synthesized in the same manner as 3b and 3X. The reaction reagents used were N-methylpiperidine (1.88 g, 1 equiv.) and 6a (10 g, 1 equiv.), and the product 6b (11.0 g) was obtained as a brown powder with a yield of 92.6%. 1 H NMR (500 MHz DMSO-d6) 8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2Hs), 3.2 (m, 5.5Hs), 2.9 (m, 2.7Hs), 2.3-2.4 (m, 2.1Hs), 1.0-1.4 (m, 9Hs). The preparation method of 6X membrane material is similar to that of 3X, with cyclopentane as solvent and drying temperature at 90 °C. The exchange process is the same as that of 1X, and the elemental analysis shows that the Br content of 6X membrane is less than 0.1 wt%.
[0090] The preferred structural intermediate 7b and the preferred structural intermediate 7X were synthesized in the same manner as 3b and 3X. The reaction reagents used were N-methylpiperidine (1.16 g, 1 equiv.) and 7a (10 g, 1 equiv.), and the product 7b (10.5 g) was obtained as a brown powder with a yield of 94.1%. 1 H NMR (500 MHz DMSO-d6) 8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2Hs), 3.2 (m, 3Hs), 2.9 (m, 1.5Hs), 2.3-2.4 (m, 2.5Hs), 1.0-1.4 (m, 5Hs). The preparation method of 7X membrane material is similar to that of 3X, the solvent is cyclopentane, and the drying temperature is 90 °C. The exchange process is the same as that of 1X, and the elemental analysis shows that the Br content of 7X membrane is less than 0.1 wt%.
[0091] The preferred structural intermediate 8b and the preferred structural intermediate 8X were synthesized in the same manner as 3b and 3X. The reaction reagents used were N-methylpiperidine (0.3 g, 1 equiv.) and 8a (10 g, 1 equiv.), and the product 7b (10.0 g) was obtained as a white-brown powder with a yield of 97.0%. 11H NMR (500 MHz DMSO-d6) 8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2Hs), 3.2 (m, 0.6Hs), 2.9 (m, 0.3Hs), 2.3-2.4 (m, 2.9Hs), 1.0-1.4 (m, 1Hs). The preparation method of 8X membrane material is similar to that of 3X, with ethylene carbonate as solvent and drying temperature at 90 °C. The exchange process is the same as that of 1X, and the elemental analysis shows that the Br content of 8X membrane is less than 0.1 wt%.
[0092] The preferred synthesis method of structure 9X-11X is as follows:
[0093] The synthesis method of polymer intermediate 9a was the same as that of 6a. The reaction substrates used were 1,1'-binaphthyl (9.9 g, 39 mmol), 6-bromo-1,1,1-trifluoro-2-heptanone (8.8 g, 36 mmol), and trifluoroacetophenone (0.69 g, 4 mmol). The reaction was terminated when the molecular weight was 180 KDa as shown by gel chromatography. The product was a light brown powder, 19 g, with a yield of 99%. 1 H NMR (500 MHzCDCl3)δ8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.1-7.3 (m, 2.3Hs), 7.1(m,0.2Hs),3.4 (m, 1.8Hs), 2.4(m,1.8Hs), 1.7(m,1.8Hs),1.2-1.4 (m, 3.6Hs). According to NMR and molecular weight data, n:m=330:36 was determined.
[0094] The synthesis method of polymer intermediate 10a was the same as that of 6a. The reaction substrates used were 1,1'-binaphthyl (9.9 g, 39 mmol), 6-bromo-1,1,1-trifluoro-2-heptanone (4.9 g, 20 mmol), and trifluoroacetophenone (3.5 g, 20 mmol). The reaction was terminated when the molecular weight was 173 KDa as shown by gel chromatography. The product was a light brown powder, 17.1 g, with a yield of 94.4%. 1 H NMR (500 MHz CDCl3) δ8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.1-7.3 (m, 3.5Hs), 7.1(m,1Hs), 3.4 (m, 1Hs), 2.4(m,1Hs), 1.7(m,1Hs),1.2-1.4 (m, 2Hs). According to NMR, molecular weight data determined n:m=187:187.
[0095] The synthesis method of polymer intermediate 11a was the same as that of 6a. The reaction substrates used were 1,1'-binaphthyl (9.9 g, 39 mmol), 6-bromo-1,1,1-trifluoro-2-heptanone (6.3 g, 36 mmol), and trifluoroacetophenone (0.99 g, 4 mmol). The reaction was terminated when the molecular weight was 142 KDa as shown by gel chromatography. The product was a light brown powder, 15.7 g, with a yield of 92.6%. 1 H NMR (500 MHz CDCl3) δ8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.1-7.3(m, 4.8Hs), 7.1(m,1.8Hs), 3.4 (m, 0.2Hs), 2.4(m,0.2Hs), 1.7(m,0.2Hs), 1.2-1.4 (m, 0.4Hs). According to NMR, molecular weight data determined n:m=36:330.
[0096] The preferred structural intermediates 9b and 9X were synthesized in the same manner as 8b and 8X. Quinuclidine (2.0 g, 1 equiv.) and 9a (10 g, 1 equiv.) were used as reaction reagents to obtain 11.3 g of product 9b, which was a brown powder with a yield of 93.9%. 1 HNMR (500 MHz DMSO-d6) 8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 2.3Hs), 7.1 (m, 0.2Hs), 3.3 (m, 5.4Hs), 3.0 (m, 1.8Hs), 2.4 (m, 1.8Hs), 1.8 (m, 5.4Hs), 1.6 (m, 1.8Hs), 1.0-1.4 (m, 4.5Hs). The preparation method of 9X membrane material is similar to that of 6X, and the exchange process is the same as that of 1X. Elemental analysis shows that the Br content of 9X membrane is less than 0.1 wt%.
[0097] The preferred structural intermediates 10b and 10X were synthesized in the same manner as 8b and 8X. The reaction reagents used were quinuclidine (1.2 g, 1 equiv.) and 9a (10 g, 1 equiv.). The product 9b (10.1 g) was obtained as a light brown powder with a yield of 93.9%. 1H NMR (500 MHz DMSO-d6) 8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m,3.5Hs), 7.1(m, 1Hs), 3.3 (m, 3Hs),3.0(m, 1Hs) 2.4(m,1Hs),1.8(m,3Hs), 1.6(m,1Hs), 1.0-1.4 (m, 2.5Hs). The preparation method of 10X membrane material is similar to that of 6x, and the exchange process is the same as that of 1X. The elemental analysis shows that the Br content of 10x membrane is less than 0.1 wt%.
[0098] The preferred structural intermediates 11b and 11X were synthesized in the same manner as 8b and 8X. Quinuclidine (0.3 g, 1 equiv.) and 9a (10 g, 1 equiv.) were used as reaction reagents. The product 9b (10.0 g) was obtained as a light brown powder with a yield of 99%. 1 H NMR (500 MHz DMSO-d6) 8.0-8.1 (m, 2H), 7.6-8.0 (m, 8Hs), 7.2-7.3 (m, 4.8Hs), 7.1 (m, 1.8Hs), 3.3 (m, 0.6Hs), 3.0 (m, 0.2Hs) 2.4 (m, 0.2Hs), 1.8 (m, 0.6Hs), 1.6 (m, 0.2Hs), 1.0-1.4 (m, 0.5Hs). The preparation method of 9X membrane material is the same as that of 6X, using ethylene carbonate as solvent, and the exchange process is the same as that of 1X. The elemental analysis shows that the Br content of 11X membrane is less than 0.1 wt%.
[0099] The preferred synthesis method of structure 12-14X is as follows:
[0100] The preferred synthesis method of intermediate 12a is as follows:
[0101] Add 9,10-diphenylanthracene (9.7 g, 29 mmol) and 7-bromo-1,1,1-trifluoro-2-octanone (8.2 g, 30 mmol) to a two-necked reaction flask A, and dissolve them in 75 mL of dichloromethane with mechanical stirring at room temperature. Cool the reaction system to 0 °C, slowly drop a trifluoromethanesulfonic acid / trifluoroacetic acid mixed solution (1:1, 35 g), and after the addition is complete, stir at 0 °C for 10 min, and move the reaction system to a 30 °C water bath. Dissolve m-terphenyl (2.2 g, 9.9 mmol) and 3-bromo-1,1,1-trifluoro-2-propanone (1.9 g, 10 mmol) in 25 mL of dichloromethane in a two-necked reaction flask B. After the temperature of the reaction flask A system reaches 30 °C, use gel chromatography to detect the molecular weight increase every half an hour. When the average molecular weight reaches 10 KDa, add the solution in the reaction flask B to the reaction system A and continue the reaction until the product molecular weight reaches 113K. The reaction solution was poured into 1000 mL of cold 1:1 methanol / water solution to precipitate a solid. The solid was collected and washed with deionized water. The solid was dried and crushed to obtain a brown powder 12a (20 g). The yield was 94.7%. 1 HNMR (500 MHz CDCl3) δ6.5-8.1 (m, 19H), 4.2 (m, 0.7Hs), 3.2 (m, 2Hs), 2.4(m,2Hs), 1.8(m,2Hs), 0.8-1.4 (m, 8Hs). NMR, molecular weight calculation gave n:m=162:54.
[0102] The preferred synthesis method of intermediate 13a is similar to that of 12a:
[0103] The solution in the two-necked reaction flask A is 9,10-diphenylanthracene (6.4 g, 19 mmol) and 7-bromo-1,1,1-trifluoro-2-octanone (5.5 g, 20 mmol), which are dissolved in 50 mL of dichloromethane with mechanical stirring at room temperature. The solution in the two-necked reaction flask B is m-terphenyl (4.5 g, 19 mmol) and 3-bromo-1,1,1-trifluoro-2-propanone (3.8 g, 20 mmol) in 50 mL of dichloromethane. The reaction is stopped when the molecular weight of the product reaches 100 KDa, and the product is 18.2 g of brown solid with a yield of 94.3%. 1 H NMR (500MHz CDCl3) δ6.5-8.1 (m, 28H), 4.2 (m, 2Hs), 3.2 (m, 2Hs), 2.4(m, 2Hs), 1.8(m,2Hs),0.8-1.4 (m, 8Hs). NMR and molecular weight calculation gave n:m=101:101.
[0104] The preferred synthesis method of intermediate 14a is similar to that of 12a:
[0105] The solution in the two-necked reaction flask A is 9,10-diphenylanthracene (3.2 g, 9.8 mmol) and 7-bromo-1,1,1-trifluoro-2-octanone (2.75 g, 10 mmol), which are dissolved in 27 mL of dichloromethane with mechanical stirring at room temperature. The solution in the two-necked reaction flask B is m-terphenyl (6.7 g, 29.3 mmol) and 3-bromo-1,1,1-trifluoro-2-propanone (5.7 g, 30 mmol) in 75 mL of dichloromethane. The reaction is stopped when the molecular weight of the product reaches 97 KDa, and the product is 16.1 g of light brown solid with a yield of 92%. 1 H NMR (500 MHz CDCl3) δ6.5-8.1 (m, 52H), 4.2 (m, 6Hs), 3.2 (m, 2Hs), 2.4(m, 2Hs),1.8(m, 2Hs), 0.8-1.4(m, 8Hs). NMR and molecular weight calculation gave n:m=54:162.
[0106] The preferred intermediate 12b and the preferred product structure 12X were synthesized in a similar manner to 1b and 1X. Trimethylamine (0.8 g, 1 equiv.) and 12a (10 g, 1 equiv.) were used as reaction substrates and the reaction temperature was 30 °C. 10.0 g of the product 12b was obtained as a brown powder with a yield of 92.3%. 1 H NMR (500 MHz DMSO-d6) δ6.5-8.1 (m, 19H), 4.2 (m, 0.7Hs), 3.2 (m, 2Hs), 3 (m, 9H), 2.3 (m, 2Hs), 1.8 (m, 2Hs), 0.8-1.4 (m, 8Hs). The preparation method of 12X membrane material is similar to that of 6X, and the exchange process is the same as that of 1X. Elemental analysis shows that the Br content of 12X membrane is less than 0.1 wt%.
[0107] The preferred intermediate 13b and the preferred product structure 13X were synthesized in a similar manner to 1b and 1X. Trimethylamine (0.6 g, 1 equiv.) and 13a (10 g, 1 equiv.) were used as reaction substrates, and the reaction temperature was 30 °C. 10.1 g of the product 13b was obtained as a brown powder with a yield of 96.3%. 1H NMR (500 MHz DMSO-d6) δ6.5-8.1 (m, 28H), 4.2 (m, 2Hs), 3.2 (m, 2Hs), 3(m,9H), 2.3(m,2Hs), 1.8(m,2Hs), 0.8-1.4(m, 8Hs). The preparation method of 13X membrane material is similar to that of 6X, and the exchange process is the same as that of 1X. Elemental analysis shows that the Br content of 13X membrane is less than 0.1 wt%.
[0108] The preferred intermediate 14b and the preferred product structure 14X were synthesized in a similar manner to 1b and 1X. Trimethylamine (0.6 g, 1 equiv.) and 14a (10 g, 1 equiv.) were used as reaction substrates, and the reaction temperature was 30 °C. 10.2 g of the product 14b was obtained as a light brown powder with a yield of 98.7%. 1 H NMR (500 MHz DMSO-d6) δ6.5-8.1 (m, 52H), 4.2 (m, 6Hs), 3.2 (m, 2Hs), 3 (m, 9H), 2.3 (m, 2Hs), 1.8)m, 2Hs), 0.8-1.4 (m, 8Hs). The preparation method of 14X membrane material is similar to that of 6X, and the exchange process is the same as that of 1X. Elemental analysis shows that the Br content of 14X membrane is less than 0.1 wt%.
[0109] The preferred synthesis method of structures 15X-17X is as follows:
[0110]
[0111] The preferred structural intermediate 15a was synthesized similarly to 12a.
[0112] Add 9,10-diphenylanthracene (9.7 g, 29 mmol) and 7-bromo-1,1,1-trifluoro-2-octanone (8.2 g, 30 mmol) to a two-necked reaction flask A, and dissolve them in 75 mL of dichloromethane with mechanical stirring at room temperature. Cool the reaction system to 0 °C, slowly drop a trifluoromethanesulfonic acid / trifluoroacetic acid mixed solution (1:1, 35 g), and stir at 0 °C for 10 min. Move the reaction system to a 30 °C water bath. Dissolve fluorene (2.6 g, 9.8 mmol) and 6-bromo-1,1,1-trifluoro-2-heptanone (2.6 g, 10 mmol) in 25 mL of dichloromethane in a two-necked reaction flask B. After the temperature of the reaction flask A system reaches 30 °C, use gel chromatography to detect the molecular weight increase every half an hour. When the average molecular weight reaches 10 KDa, add the solution in the reaction flask B to the reaction system A and continue the reaction until the product molecular weight reaches 65K. The reaction solution was poured into 1000 mL of cold 1:1 methanol / water solution to precipitate a solid. The solid was collected and washed with deionized water. The product was dried and crushed to obtain a brown-yellow powder 15a (18.7 g) with a yield of 88.3%. 1 H NMR (500 MHz CDCl3) δ6.5-8.1 (m, 54Hs), 3.8 (m, 2Hs), 3.2 (m, 8Hs), 2.4(m,8Hs), 1.8(m,8Hs), 0.6-1.4 (m, 30Hs). NMR and molecular weight calculation gave n:m=30:90.
[0113] The preferred structural intermediate 16a was synthesized similarly to 15a.
[0114] The solution in the two-necked reaction flask A was 9,10-diphenylanthracene (6.4 g, 19.5 mmol), 7-bromo-1,1,1-trifluoro-2-octanone (5.5 g, 20 mmol), and 50 mL of dichloromethane. The solution in the two-necked reaction flask B was fluorene (3.2 g, 19.5 mmol), 6-bromo-1,1,1-trifluoro-2-heptanone (5.2 g, 20 mmol), and 50 mL of dichloromethane. The reaction was terminated when the molecular weight of the reaction product reached 45 KDa. The product was a brown-yellow powder 16a (17.3 g) with a yield of 89%. 1 H NMR (500 MHz CDCl3) δ6.5-8.1 (m, 22Hs), 3.8 (m, 2Hs), 3.2 (m, 4Hs), 2.4 (m, 4Hs), 1.8 (m, 4Hs), 0.6-1.4 (m, 14Hs). NMR and molecular weight calculation gave n:m=45:45.
[0115] The preferred structural intermediate 17a was synthesized similarly to 15a.
[0116] The solution in the two-necked reaction flask A was 9,10-diphenylanthracene (3.2 g, 9.8 mmol), 7-bromo-1,1,1-trifluoro-2-octanone (2.7 g, 10 mmol), and 25 mL of dichloromethane. The solution in the two-necked reaction flask B was fluorene (4.9 g, 29 mmol), 6-bromo-1,1,1-trifluoro-2-heptanone (7.8 g, 30 mmol), and 75 mL of dichloromethane. The reaction was terminated when the molecular weight of the reaction product reached 97 KDa. The product was a brown-yellow powder 17a (15.9 g) with a yield of 89.8%. 1 H NMR (500 MHz CDCl3) δ6.5-8.1 (m, 34Hs), 3.8 (m, 6Hs), 3.2 (m, 6Hs), 2.4 (m, 8Hs), 1.8 (m, 8Hs), 0.6-1.4 (m, 26Hs). NMR, molecular weight calculation gave n:m=54:162.
[0117] The preferred intermediate 15b and the preferred product structure 15X were synthesized in a similar manner to 1b and 1X. The reaction substrates were methylpiperidine (1.8 g, 1 equiv.) and 15a (10 g, 1 equiv.), and the reaction temperature was 60 °C. The product 15b was obtained in an amount of 10.0 g as a brown powder with a yield of 84.7%. 1 H NMR (500 MHz DMSO-d6) δ6.5-8.1 (m, 54Hs), 3.8 (m, 2Hs), 3.2 (m, 24Hs), 2.8 (m, 12Hs), 2.4 (m, 8Hs), 1.8 (m, 8Hs), 0.6-1.4 (m, 54Hs). The preparation method of 15X membrane material is similar to that of 6X, and the exchange process is the same as that of 1X. Elemental analysis shows that the Br content of 15X membrane is less than 0.1 wt%.
[0118] The preferred intermediate 16b and the preferred product structure 16X were synthesized in a similar manner to 1b and 1X. Methylpiperidine (2.0 g, 1 equiv.) and 16a (10 g, 1 equiv.) were used as reaction substrates, and the reaction temperature was 60 °C. 10.8 g of the product 16b was obtained as a brown powder with a yield of 90.1%. 1H NMR (500 MHz DMSO-d6) δ6.5-8.1 (m, 22Hs), 3.8 (m, 2Hs), 3.2 (m, 12Hs), 2.8 (m, 6Hs), 2.4 (m, 4Hs), 1.8 (m, 4Hs), 0.6-1.4 (m, 26Hs). The preparation method of 16X membrane material is similar to that of 6X, and the exchange process is the same as that of 1X. Elemental analysis shows that the Br content of 16X membrane is less than 0.1 wt%.
[0119] The preferred intermediate 17b and the preferred product structure 17X were synthesized in a similar manner to 1b and 1X. Methylpiperidine (2.2 g, 1 equiv.) and 17a (10 g, 1 equiv.) were used as reaction substrates, and the reaction temperature was 60 °C. The product 17b (11.8 g) was obtained as a brown powder with a yield of 96.9%. 1 H NMR (500 MHz DMSO-d6) δ6.5-8.1 (m, 34Hs), 3.8 (m, 6Hs), 3.2 (m, 24Hs), 2.8 (m, 12Hs), 2.4 (m, 8Hs), 1.8 (m, 8Hs), 0.6-1.4 (m, 50Hs). The preparation method of 17X membrane material is similar to that of 6X, and the exchange process is the same as that of 1X. Elemental analysis shows that the Br content of 17X membrane is less than 0.1 wt%.
[0120] The synthesis methods of Examples 18-23 are as follows:
[0121]
[0122] The preferred synthesis method of polymer structure 18X-20X is shown in the following formula:
[0123]
[0124] The preferred synthesis method of intermediate 18a is as follows:
[0125] Add 1,1'-binaphthyl (6.6 g, 26.1 mmol) and 6-bromo-1,1,1-trifluoro-2-hexanone (6.6 g, 26.8 mmol) to a two-necked reaction flask A and dissolve them in 67 mL of dichloromethane with mechanical stirring at room temperature. Cool the reaction system to 0 °C and slowly drop a trifluoromethanesulfonic acid / trifluoroacetic acid mixed solution (1:1, 35 g). After the addition is complete, stir at 0 °C for 10 min and move the reaction system to a 30 °C water bath. Dissolve 9,9-dimethylfluorene (2.5 g, 12.9 mmol) and 1,1,1-trifluoro-2-heptanone (2.4 g, 13.2 mmol) in 33 mL of dichloromethane in a two-necked reaction flask B. After the temperature of the reaction bottle A system reached 30 °C, the molecular weight growth was detected by gel chromatography every half an hour. When the average molecular weight reached 10 KDa, the solution in the reaction bottle B was added to the reaction system A to continue the reaction until the molecular weight of the product reached 265K. The reaction solution was poured into 1000 mL of cold 1:1 methanol / water solution to precipitate a solid. The solid was collected, washed three times with ethanol, and then redissolved in 100 mL of tetrahydrofuran. Dimethylamine (11.8 g, 261 mmol) was added, and the reaction was stirred for 48 hours. The solid was precipitated in anhydrous ether at 0 °C, dried, and the crushed product was a light brown powder 18a (15.1 g) with a yield of 87.7%. 1 H NMR (500 MHz CDCl3) δ8.0-8.1 (m, 6Hs), 7.6-8.0 (m, 18Hs), 7.3-7.4 (m, 2Hs), 7.2-7.3 (m, 4Hs), 2.4 (m, 6Hs), 2.2 (m, 12Hs), 1.7 (m, 6Hs), 0.6-1.4 (m, 27Hs). NMR, molecular weight calculation gave n:m=402:203.
[0126] The preferred intermediate 19a was synthesized similarly to 18a.
[0127] The solution in the two-mouth reaction flask A was 1,1'-binaphthyl (5.0 g, 19.5 mmol), 6-bromo-1,1,1-trifluoro-2-hexanone (4.9 g, 20 mmol), and 67 mL of dichloromethane. The solution in the two-mouth reaction flask B was 9,9-dimethylfluorene (3.8 g, 19.5 mmol), 1,1,1-trifluoro-2-heptanone (3.6 g, 20 mmol), and 33 mL of dichloromethane. The reaction was quenched when the molecular weight reached 253 KDa, and dimethylamine (8.8 g, 195 mmol) was used for post-treatment. The product was a light brown powder 19a (13.6 g) with a yield of 87.7%. 1H NMR (500 MHz CDCl3) δ8.0-8.1 (m, 4Hs), 7.6-8.0 (m, 10Hs), 7.3-7.4 (m, 2Hs), 7.2-7.3 (m, 2Hs), 2.4 (m, 4Hs), 2.2 (m, 6Hs), 1.7 (m, 4Hs), 0.6-1.4 (m, 21Hs). NMR, molecular weight calculation gave n:m=302:302.
[0128] The preferred intermediate 20a was synthesized similarly to 18a.
[0129] The solution in the two-mouth reaction flask A was 1,1'-binaphthyl (3.3 g, 13 mmol), 6-bromo-1,1,1-trifluoro-2-hexanone (3.3 g, 13.4 mmol), and 33 mL of dichloromethane. The solution in the two-mouth reaction flask B was 9,9-dimethylfluorene (5.0 g, 26 mmol), 1,1,1-trifluoro-2-heptanone (4.8 g, 26.6 mmol), and 67 mL of dichloromethane. The reaction was quenched when the molecular weight reached 211 KDa, and dimethylamine (5.9 g, 131 mmol) was used for post-treatment. The product was a light brown powder 20a (13.6 g) with a yield of 89.3%. 1 H NMR (500 MHz CDCl3) δ8.0-8.1 (m, 6Hs), 7.6-8.0 (m, 12Hs), 7.3-7.4 (m, 4Hs), 7.2-7.3 (m, 2Hs), 2.4 (m, 6Hs), 2.2 (m, 6Hs), 1.7 (m, 6Hs), 0.6-1.4 (m, 36Hs). NMR, molecular weight calculation gave n:m=181:362.
[0130] The preferred intermediate 18b, preferred structure 18X is synthesized similarly to 1a, 1X:
[0131] The reaction substrate 18a (10 g, 1 equiv.) was dissolved in 100 mL of tetrahydrofuran / methanol (1:1) solution. N1,N4-bis(6-bromohexyl)-N1-methanilino-N1,N4,N4-trimethylbutane-1,4-diammonium (47.6 g, 5 equiv.) was dissolved in 200 mL of tetrahydrofuran / methanol mixed solvent (1:1) and the 18a solution was added to the solution at 60 °C. The reaction was continued for 2 days. The reaction system was cooled to 30 °C and trimethylamine (18 g, 20 equiv.) was added. The reaction was stirred for another 2 days. The reaction solution was concentrated and added to a dialysis bag (50K molecular weight permeable) and washed with deionized water until the ionic conductivity of the washing solution was the same as that of deionized water. After drying and powdering, the product 18b was obtained as a light brown powder of 18.5 g with a yield of 90.7%. 1 H NMR (500MHz DMSO-d6) δ8.0-8.1 (m, 6Hs), 7.6-8.0 (m, 18Hs), 7.3-7.4 (m, 2Hs), 7.2-7.3 (m, 4Hs), 3.3 (m, 28Hs), 3.1 (m, 54Hs), 2.4 (m, 6Hs), 1.7 (m, 30Hs), 0.6-1.4 (m, 39Hs). The preparation method of 18X membrane material is similar to that of 6X, using cyclopentane as solvent, and the exchange process is the same as that of 1X. Elemental analysis shows that the Br content of 18X membrane is less than 0.1 wt%.
[0132] The preferred intermediate 19b, the preferred structure 19X is synthesized similarly to 18a, 18X:
[0133] The reaction substrate 19a (10 g, 1 equiv.) was dissolved in 100 mL of tetrahydrofuran / methanol (1:1) solution. N1,N4-bis(6-bromohexyl)-N1-methanilino-N1,N4,N4-trimethylbutane-1,4-diammonium (37.3 g, 5 equiv.) was dissolved in 200 mL of tetrahydrofuran / methanol mixed solvent (1:1) and the 19a solution was added to this solution at 60 °C. The reaction was continued for 2 days. After the reaction system was cooled to 30 °C, trimethylamine (14 g, 20 equiv.) was added and the reaction was stirred for another 2 days. The reaction solution was concentrated and added to a dialysis bag (50K molecular weight permeable) and washed with deionized water until the ionic conductivity of the washing solution was the same as that of deionized water. After drying and powdering, the product 18b was obtained as a light brown powder of 16.5 g with a yield of 90.9%. 1H NMR (500MHz DMSO-d6) δ8.0-8.1 (m, 4Hs), 7.6-8.0 (m, 10Hs), 7.3-7.4 (m, 2Hs), 7.2-7.3 (m, 2Hs), 3.3 (m, 14Hs), 3.1 (m, 27Hs), 2.4 (m, 4Hs), 1.7 (m, 16Hs), 0.6-1.4 (m, 27Hs). The preparation method of 19X membrane material is the same as that of 18X, and the exchange process is the same as that of 1X. The elemental analysis shows that the Br content of 19X membrane is less than 0.1wt%.
[0134] The preferred intermediate 20b, the preferred structure 20X is synthesized similarly to 19a, 19X:
[0135] The reaction substrate 20a (10 g, 1 equiv.) was dissolved in 100 mL of tetrahydrofuran / methanol (1:1) solution. N1,N4-bis(6-bromohexyl)-N1-methanilino-N1,N4,N4-trimethylbutane-1,4-diammonium (26.6 g, 5 equiv.) was dissolved in 200 mL of tetrahydrofuran / methanol mixed solvent (1:1) and the 20a solution was added to this solution at 60 °C. The reaction was continued for 2 days. After the reaction system was cooled to 30 °C, trimethylamine (10 g, 20 equiv.) was added and the reaction was stirred for another 2 days. The reaction solution was concentrated and added to a dialysis bag (50K molecular weight permeable) and washed with deionized water until the ionic conductivity of the washing solution was the same as that of deionized water. After drying and powdering, the product 20b was obtained as a light brown powder of 13.5 g with a yield of 85.4%. 1H NMR (500MHz DMSO-d6) δ8.0-8.1 (m, 6Hs), 7.6-8.0 (m, 12Hs), 7.3-7.4 (m, 4Hs), 7.2-7.3 (m, 2Hs), 3.3 (m, 14Hs), 3.1 (m, 27Hs), 2.4 (m, 6Hs), 1.7 (m, 18Hs), 0.6-1.4 (m, 42Hs). The preparation method of 20X membrane material is the same as that of 19X, and the exchange process is the same as that of 1X. The elemental analysis shows that the Br content of 20X membrane is less than 0.1wt%.
[0136] The preferred synthesis methods of structures 21X-23X are as follows:
[0137]
[0138] The preferred intermediate 21a is synthesized similarly to the preferred structural intermediate 18a:
[0139] The two-necked reaction flask A contained 1,1'-binaphthyl (6.6 g, 26.1 mmol) and 7-bromo-1,1,1-trifluoro-2-heptanone (7.0 g, 26.8 mmol), which were dissolved in 67 mL of dichloromethane with mechanical stirring at room temperature. The solution in the two-necked reaction flask B contained biphenyl (1.98 g, 12.9 mmol), 7-bromo-1,1,1-trifluoro-2-heptanone (3.4 g, 13.2 mmol) and 33 mL of dichloromethane. The reaction was terminated when the molecular weight of the product reached 696 K. After washing three times with ethanol, it was redissolved in 100 mL of tetrahydrofuran, and dimethylamine (11.8 g, 261 mmol) was added. The reaction was stirred for 48 hours, and the solid was precipitated in anhydrous ether at 0 °C. The solid was dried and crushed to obtain a light brown powder 21a (16.6 g) with a yield of 92.7%. 1 H NMR (500 MHz CDCl3) δ8.0-8.1 (m, 4Hs), 7.6-8.0 (m, 20Hs), 7.3-7.4 (m, 4Hs), 7.2-7.3 (m, 4Hs), 2.4 (m, 6Hs), 2.2 (m, 18Hs), 1.7 (m, 6Hs), 0.6-1.4 (m, 27Hs). NMR, molecular weight calculation gave n:m=1002:501.
[0140] The preferred intermediate 22a was synthesized similarly to the preferred structural intermediate 18a:
[0141] The two-necked reaction flask A contained 1,1'-binaphthyl (4.96 g, 19.5 mmol) and 7-bromo-1,1,1-trifluoro-2-heptanone (5.2 g, 20 mmol), which were dissolved in 50 mL of dichloromethane with mechanical stirring at room temperature. The solution in the two-necked reaction flask B contained biphenyl (3.0 g, 19.5 mmol), 7-bromo-1,1,1-trifluoro-2-heptanone (5.2 g, 20 mmol) and 50 mL of dichloromethane. The reaction was terminated when the molecular weight of the product reached 745 K. After washing three times with ethanol, it was redissolved in 100 mL of tetrahydrofuran, and dimethylamine (8.8 g, 195 mmol) was added. The reaction was stirred for 48 hours, and a solid was precipitated in anhydrous ether at 0 °C. The solid was dried and crushed to obtain a light brown powder 22a (16.1 g) with a yield of 92.5%. 1H NMR (500 MHz CDCl3) δ8.0-8.1 (m, 2Hs), 7.6-8.0 (m, 12Hs), 7.3-7.4 (m, 4Hs), 7.2-7.3 (m, 2Hs), 2.4 (m, 4Hs), 2.2 (m, 12Hs), 1.7 (m, 4Hs), 0.6-1.4 (m, 16Hs). NMR, molecular weight calculation gave n:m=835:835.
[0142] The preferred intermediate 23a was synthesized similarly to the preferred structural intermediate 18a:
[0143] The two-necked reaction flask A contained 1,1'-binaphthyl (3.3 g, 13.1 mmol) and 7-bromo-1,1,1-trifluoro-2-heptanone (3.5 g, 13.4 mmol), which were dissolved in 33 mL of dichloromethane with mechanical stirring at room temperature. The solution in the two-necked reaction flask B contained biphenyl (4.0 g, 26 mmol), 7-bromo-1,1,1-trifluoro-2-heptanone (6.9 g, 26.6 mmol) and 67 mL of dichloromethane. The reaction was terminated when the molecular weight of the product reached 654 K. After washing with ethanol three times, it was redissolved in 100 mL of tetrahydrofuran, and dimethylamine (5.9 g, 130 mmol) was added. The reaction was stirred for 48 hours, and the solid was precipitated in anhydrous ether at 0 °C. The solid was dried and crushed to obtain a light brown powder 23a (16.1 g) with a yield of 93.9%. 1 H NMR (500 MHz CDCl3) δ8.0-8.1 (m, 2Hs), 7.6-8.0 (m, 16Hs), 7.3-7.4 (m, 8Hs), 7.2-7.3 (m, 2Hs), 2.4 (m, 6Hs), 2.2 (m, 18Hs), 1.7 (m, 6Hs), 0.6-1.4 (m, 24Hs). NMR, molecular weight calculation gave n:m=518:1036.
[0144] The preferred intermediate 21b, preferred structure 21X is synthesized similarly to 19a, 19X:
[0145] The reaction substrate 21a (10 g, 1 equiv.) was dissolved in 100 mL of tetrahydrofuran / methanol (1:1) solution. 4,4'-(Dimethyl-1,4-azobis(N-(4-bromobutyl)-N,N-dimethylbutane-1-ammonium) (81 g, 5 equiv.) was dissolved in 600 mL of tetrahydrofuran / methanol mixed solvent (1:1), and the 21a solution was added to the solution at 60 °C. The reaction was continued for 2 days. After the reaction system was cooled to 30 °C, trimethylamine (25.5 g, 20 equiv.) was added and the reaction was stirred for another 2 days. The reaction solution was concentrated and added to a dialysis bag (50 K molecular weight permeable) and washed with deionized water until the ionic conductivity of the washing solution was the same as that of deionized water. The product 21b was dried and powdered to obtain 26.5 g of light brown powder with a yield of 96.4%. 1H NMR (500MHz DMSO-d6) δ8.5 (m, 4Hs), 7.6-8.2 (m, 20Hs), 7.3-7.4(m,8Hs), 7.2-7.3(m,2Hs),3.2-3.4(m,54Hs), 3.0(m,99Hs), 2.4(m, 6Hs), 1.2-1.8(m,72Hs). The preparation method of 21X membrane material is the same as 19X, and the exchange process is the same as 1X. The elemental analysis shows that the Br content of 21X membrane is less than 0.1 wt%.
[0146] The preferred intermediate 22b, preferred structure 22X is synthesized similarly to 19a, 19X:
[0147] The reaction substrate 22a (10 g, 1 equiv.) was dissolved in 100 mL of tetrahydrofuran / methanol (1:1) solution. 4,4'-(Dimethyl-1,4-azolyl)bis(N-(4-bromobutyl)-N,N-dimethylbutane-1-ammonium) (84 g, 5 equiv.) was dissolved in 600 mL of tetrahydrofuran / methanol mixed solvent (1:1), and the 22a solution was added to the solution at 60 °C. The reaction was continued for 2 days. After the reaction system was cooled to 30 °C, trimethylamine (26.5 g, 20 equiv.) was added and the reaction was stirred for another 2 days. The reaction solution was concentrated and added to a dialysis bag (50 K molecular weight permeable) and washed with deionized water until the ionic conductivity of the washing solution was the same as that of deionized water. The product 22b was dried and powdered to obtain 27.5 g of light brown powder with a yield of 97.7%. 1H NMR (500MHz DMSO-d6) δ8.5 (m, 2Hs), 7.6-8.2 (m, 12Hs), 7.2-7.4(m,6Hs), 3.2-3.4(m,36Hs),3.0(m,66Hs), 2.4(m, 4Hs), 1.2-1.8(m,48Hs). The preparation method of 22X membrane material is the same as that of 19X, and the exchange process is the same as that of 1X. The elemental analysis shows that the Br content of 22X membrane is less than 0.1 wt%.
[0148] The preferred intermediate 23b, preferred structure 23X is synthesized similarly to 19a, 19X:
[0149] The reaction substrate 23a (10 g 1 equiv.) was dissolved in 100 mL of tetrahydrofuran / methanol (1:1) solution. 4,4'-(Dimethyl-1,4-azobis(N-(4-bromobutyl)-N,N-dimethylbutane-1-ammonium) (89 g, 5 equiv.) was dissolved in 600 mL of tetrahydrofuran / methanol mixed solvent (1:1), and the 23a solution was added to the solution at 60 °C. The reaction was continued for 2 days. After the reaction system was cooled to 30 °C, trimethylamine (26.5 g, 20 equiv.) was added and the reaction was stirred for another 2 days. The reaction solution was concentrated and added to a dialysis bag (50 K molecular weight permeable) and washed with deionized water until the ionic conductivity of the washing solution was the same as that of deionized water. The product 23b was dried and powdered to obtain 28.5 g of light brown powder with a yield of 97.5%. 1H NMR (500MHz DMSO-d6) δ8.5 (m, 2Hs), 7.6-8.2 (m, 16Hs), 7.2-7.4(m,10Hs), 3.2-3.4(m,54Hs),3.0(m,99Hs), 2.4(m, 6Hs), 1.2-1.8(m,72Hs). The preparation method of 22X membrane material is the same as that of 19X, and the exchange process is the same as that of 1X. The elemental analysis shows that the Br content of 22X membrane is less than 0.1 wt%.
[0150] The molecular weight test method during the synthesis process is as follows:
[0151] Take a small amount of sample (10 mg) and dissolve it in chromatographic grade tetrahydrofuran (1 mL), filter it, take 50 μL of the filtrate, remove the obvious bubbles in the injection needle, and inject 10 μL of the liquid into the liquid chromatograph EClassical 3100, using gel permeation chromatography, tetrahydrofuran as the mobile phase, the flow rate is 1 mL / min, 30 ℃. n=50-1800; typical (intermediate 1a-5a) spectrum is as follows Figure 1 shown.
[0152] The NMR test methods involved in the synthesis process are as follows:
[0153] 10 mg of sample was dissolved in 1 mL of corresponding deuterated solvent, and the test equipment used was Burker 500MHz NMR equipment, T1=2S, and scanned at least 16 times. The NMR of the obtained preferred structure polymer 22X is as follows: Figure 2 shown.
[0154] Test Example 1:
[0155] The polymers 1X-23X prepared in Examples 1-23 were tested for performance, and the test method was as follows:
[0156] AC impedance test:
[0157] The 1X-23X membrane was subjected to electrochemical impedance spectroscopy (EIS) testing using an electrochemical workstation (CHI660E). The membrane sample (4 cm long, 1 cm wide) was properly fixed in a special electrochemical test cell (4 electrodes, platinum as the electrode material) to ensure that the membrane was in close contact with the test cell electrode system. Before the test, the test solution (such as an electrolyte solution of a specific concentration) was injected into the test cell to fully infiltrate the membrane sample. If the test stability is not at room temperature, the sample was allowed to balance in the electrolyte for at least 30 minutes to allow the sample to reach the test temperature. The test parameters of the electrochemical workstation were set, and the scanning frequency range was set to 1*10 6 HZ to 0.1 HZ, AC excitation signal amplitude of 2 sec, voltage of 100 mV. The impedance value is obtained when the phase angle is closest to 0°, and the ionic conductivity is calculated according to the sample size and thickness.
[0158] Tensile strength test:
[0159] The tensile strength of the membrane samples was tested using a universal tensile machine (Instron-3367, Instron, USA). The membrane samples were precisely cut into standard dumbbell-shaped specimens, and their dimensions strictly conformed to the national standard GB / T 1040.3-2 (length 150 mm, width 20 mm, thickness 20-60 μm). The specimens were installed between the upper and lower clamps of the universal tensile machine, and the tensile rate of the universal tensile machine was set to 50 mm / min. After starting the test, the tensile force acting on the specimen during the stretching process and the corresponding elongation were monitored and recorded in real time. Until the specimen broke, the tensile strength of the membrane was calculated based on the recorded data (the tensile force at break divided by the original cross-sectional area of the specimen).
[0160] The material performance test results are shown in Table 1 below:
[0161] Table 1 Test results of mechanical strength and ionic conductivity of the preferred structure
[0162]
[0163] Note: Controls 1-3 are from the literature: Nat Commun 10, 2306 (2019), patent US11230626B2; Control 4 is from Nat Energy 4, 392–398 (2019); Controls 5-7 are from ACS Macro Lett 4, 814−818 (2015), patent CN111647138 B, patent US11173456B2; Controls 8-9 are from patent US10435504B2; Controls 10-12 are from ACS Macro Lett, 6, 566−570 (2017).
[0164] Figure 3 This is a comparison chart of material performance test data of preferred polymers 18X, 19X, and 21X, wherein the lower left corner of the chart shows the data of each control group.
[0165] The test results show that ion exchange membrane materials with large pi systems exhibit excellent mechanical strength (e.g. 1-6, 18-23) and the molecular weight is positively correlated with the mechanical strength, but the increase in mechanical strength caused by the increase in molecular weight is limited when n+m exceeds 500. The structure of the ionic functional groups An-, CA+ and LK is very important for ionic conductivity. Compared with the control groups in other literature / patents, the comparison of the side chain structure based on the skeleton structure of the large pi group and the preferred ionic group can effectively enhance the electrolyte material's conductivity and mechanical strength at the same time, thereby breaking the trade-off between the mechanical stability and electrochemical performance of the material in this type of material.
[0166] Application Example 1
[0167] The film made of polymer 22X obtained in Example 22 was used to perform anion exchange membrane water electrolysis test (X=OH during electrolysis). The test process, battery structure and actual diagram are shown in the following figure. Figure 4 As shown:
[0168] Cut to the appropriate size (usually 5*5cm 2) of the circular PTFE gasket, electrode and the anion exchange membrane that has been exchanged; fix the current collecting plate with the cathode flow channel plate through the positioning hole with bolts and put it into the fixture; place the PTFE on the flow channel area and put the cathode electrode in the hollow space in the middle; pass the anode flow channel plate and the current collecting plate through the positioning holes to cover the PTFE, tighten and fix the entire test cell with nuts and bolts through the positioning holes, and adjust the torque of the test cell with a torque wrench; connect the installed cell to the corresponding inlet and outlet water pipes according to the anode and cathode, turn on the circulation pump to set the flow rate to circulate the heated electrolyte into the system; connect the positive and negative poles of the power supply and the voltage, current and temperature detection device to the test cell, set the program and current size, turn on the pump circulation at the same time, heat the system to the corresponding temperature, turn on the power and the corresponding program, start the electrolysis experiment, and collect operating parameters such as temperature, current, and voltage.
[0169] Figure 5 The voltage data of 22OH after running for 1000 hours in the electrolytic water test environment is shown.
[0170] In the electrolysis test in the figure, NiFeSOx oxide is used as a hydrogen evolution catalyst attached to the nickel mesh, and NiMo oxygen evolution catalyst is attached to the nickel mesh. The operating environment is 1 M KOH, 60 ℃. After 1000 hours of testing, the back pressure valve is opened to make the gas pressure at the hydrogen production end reach 3 Mpa. After continuous operation for 200 hours, there is no gas leakage or liquid leakage in the system. The electrolytic cell test shows the chemical and mechanical stability of the membrane of the present invention and provides excellent electrolytic performance.
[0171] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A highly conjugated block polymer, characterized in that: It contains the structural unit shown in the following formula (I): (I) wherein n, m are the number of repeating units; n is an integer from 1 to 2000; m is an integer from 1 to 2000; Ar1 is selected from one of the following structural fragments: , , or ; Ar2 is selected from one of the following structural fragments: The values of x1 and x2 are 0-10; LK1 and LK2 are linking groups, each independently selected from or ; is an ionic group, where Select one of the following structural fragments: Select one of the following structural fragments: R1 is an ionic group or a nonionic group; when R1 is an ionic group, its definition is the same as When R1 is a nonionic group, it is selected from one of the following structural fragments: 。 2. The highly conjugated block polymer according to claim 1, characterized in that Ar1 is selected from or .
3. The highly conjugated block polymer according to claim 2, characterized in that The EWG is selected from one of the following structural fragments: 。 4. The highly conjugated block polymer according to claim 3, characterized in that The highly conjugated block polymer is selected from one of the following structural formulas: 。 5. A method for preparing a highly conjugated block polymer as claimed in any one of claims 1 to 4, characterized in that: When LK1 and LK2 are When, the method comprises the following steps: Step (1), Ar1, EWG (CO) Rii, Ar2, and EWG (CO) R1 are mixed and dissolved in a solvent, and reacted under the action of a catalyst to generate a precursor; Where Rii is ; Step (2), dissolving the precursor in a solvent, adding a nucleophilic reagent for reaction, quenching, eluting, and then adding a salt solution for ion exchange to obtain the highly conjugated block polymer; 。 6. A method for preparing a highly conjugated block polymer as claimed in any one of claims 1 to 4, characterized in that: When LK1 and LK2 are independently selected from or When, the preparation method comprises the following steps: Step (1), Ar1, EWG (CO) Rii, Ar2, and EWG (CO) R1 are mixed and dissolved in a solvent, and reacted under the action of a catalyst to generate a polymer precursor; Where Rii is ; Step (2), dissolving the precursor in an organic solvent for functionalization to obtain an intermediate, then mixing it with a linker, adding a nucleophilic reagent to react, quenching and eluting, and then adding a salt solution for ion exchange to obtain the highly conjugated block polymer; Wherein Y6 and Y7 are independently selected from F, Cl, Br or .
7. The preparation method according to claim 5 or 6, characterized in that: The solvent in step (1) is one of dichloromethane, chloroform, tetrachloromethane or chlorobenzene.
8. The preparation method according to claim 5 or 6, characterized in that: The catalyst in step (1) is one or a mixture of concentrated sulfuric acid, concentrated nitric acid, trifluoroacetic acid, and trifluoromethanesulfonic acid.
9. An anion exchange membrane, characterized in that The method is prepared from the highly conjugated block polymer according to any one of claims 1 to 4.
10. The anion exchange membrane according to claim 9, characterized in that The preparation method is as follows: a highly conjugated block polymer is dissolved in an organic solvent to prepare a slurry, which is then coated on a substrate by a roll-to-roll process, screen printing or doctor blade casting, and the organic solvent in the slurry is evaporated by drying to solidify the highly conjugated block polymer on the surface of the substrate to form a film, which is then peeled off to obtain the anion exchange membrane.
11. Use of the anion exchange membrane as claimed in claim 9 in electrochemistry.
12. The use according to claim 11, characterized in that: The applications include: preparing fuel cells, preparing supercapacitors, preparing organic liquid flow batteries, electrolyzing water, electrolyzing CO2, electrolyzing CO, purifying CO2, separating heavy metals, electrically driven CO2 enrichment, recovering lithium salts, and serving as metal-air battery separators.
Citation Information
Patent Citations
Polymers and methods for their manufacture
US10435504B2
Anion exchange polymers and anion exchange membranes incorporating same
US11173456B2
Crosslinking of hydroxide stable, polybenzimidazoliums and polyimidazoliums membranes and ionomers
US11230626B2
Anion exchange membrane containing flexible chain segment and based on polymerization of piperidone and aromatic hydrocarbon as well as preparation method and application of anion exchange membrane
CN112175170A
Anion exchange membrane containing twisted aryl and ketone monomer, adhesive, preparation and application
CN113659180A